Enhancement of eddy current testing probe for crack detection and lift-off compensation - Faraj, Moneer A (2019)
Pipelines are subject to defect and corrosion which in turn can cause leakage and environmental damage. Eddy current testing has proved to be an effective technique to detect defects occurring in the pipe wall. In the past two decades, few types of eddy current probes were developed for pipe inspection that included bobbin coil probe, rotating probe and array probe but still, each of these probes have their own limitations. Among these types, the bobbin probes are widely used in industry to inspect tube and pipeline. In order to obtain deeper penetration depth, lower excitation frequencies must be used since penetration depth is inversely proportional to the square root of the excitation frequency. However, in conventional bobbin eddy current probes, a drop in the signal-to-noise ratio (SNR) was observed at lower frequencies, as well as lift off effects that reduced the accuracy detection of the probe. To address these problems, this thesis presents a new probe design for crack detection with accurate depth defect measurement. The bobbin coil used in the magnetization of pipe utilized a 30 kHz excitation signal and the GMR sensor array was used as a detector to pick up the field leakages from the pipe cracks (axial and hole). The response surface methodology (RSM) was utilized to optimize the proposed probe design parameters to increase the probability of defect detections in 55 mm diameter carbon steel pipe. Besides that, the intelligent compensation technique based on fuzzy logic was used to overcome the influence of lift-off for accurate defect measurement. The response surface methodology showed that the highest desirability value of 0.679 with optimum parameters of the proposed probe were 6 GMR sensors array, lift-off of 2 mm and height of coil of 10 mm that increased the rate of detection defects. The experimental result showed that the accuracy of the probe design inspection was 100 % for axial and hole defects using minimum number of 6 GMR sensors. Compared with the previous work design using 6 GMR sensor showed that the rate of defect detection was 80%. In addition, the proposed error compensation technique proved that there were reductions in the effect of lift-off and also enhanced the overall probe performance accuracy. Validation of the proposed probe through comparison with a commercial probe clearly indicated that the proposed probe can significantly minimized the effect of lift-off in eddy current testing within 7.2 % of error due for each 1 mm of lift-off. Moreover, the experimental results were compared with the previous compensation technique where the errors due to 2 mm of lift-off were within 14.3 % and 18.3%, for the proposed technique and previous compensation technique, respectively. The proposed probe can detect both hole and axial defects, offers a high sensitivity over a wide range of frequencies, can potentially provide extremely high rate defects detection and improve the accuracy of depth defect measurement.